Influence of Synovial Fluid on Human Osteoblasts: An In Vitro Study - Thomas F. Fuchs; Wolf Petersen; Thomas Vordemvenne; Richard Stange; Michael Raschke; Jürgen R.J. Paletta (The Scientific World Journal)
Osseous graft healing at the tendon bone interface after anterior cruciate ligament (ACL) reconstruction is unsatisfactory in 10—25%, depending on the evaluation criteria or the kind of graft used for reconstruction. Mechanical as well as biological aspects are currently discussed. Since osteoblasts play an important role in the osseous integration of an ACL graft, we hypothesize that synovial fluid (SF), when entering the bone tunnel, has an inhibitory effect on osteoblasts. In order to verify this hypothesis, human osteoblasts (p3) were incubated in the presence of SF or partially purified SF. Proliferation was assayed using MTT or BrdU assay. Gene expression of osteoblast markers (alkaline phosphatase, collagen I, and osteocalcin) were determined by TaqMan analysis. In the control group, SF was exchanged by fetal calf serum (FCS). The results showed osteoblast proliferation in the presence of SF as well as in partially purified heat-pretreated synovial fluid. Native SF induced alkaline phosphatase and collagen I gene expression. No induction of the osteocalcin gene was observed in the experiment. These results were comparable to that obtained with FCS. These findings suggest that SF stimulated proliferation of osteoblasts in vitro. This effect is mediated, in part, by heat-stable components of SF. In addition, the expression of osteoblast marker genes alkaline phosphatase and collagen I, but not osteocalcin, was induced by SF. Therefore, problems associated with cruciate ligament reconstruction might be due to the inhibition of osteoblast differentiation. If so, this is not a specific attribute of SF, but also applies to serum.